East Indian sandalwood (Santalum album L.) oil confers neuroprotection and geroprotection in Caenorhabditis elegans via activating SKN-1/Nrf2 signaling pathway. Issue 59 (2nd October 2018) - Mohankumar, A.; Shanmugam, G.; Kalaiselvi, D.; Levenson, C.; Nivitha, S.; Thiruppathi, G.; Sundararaj, P.
Abstract : East Indian Sandalwood Oil (EISO) has diverse beneficial effects and has been used for thousands of years in traditional folk-medicine for treatment of different human ailments. Abstract : East Indian Sandalwood Oil (EISO) has diverse beneficial effects and has been used for thousands of years in traditional folk-medicine for treatment of different human ailments. However, there has been no in-depth scientific investigation to decipher the neuroprotective and geroprotective mechanism of EISO and its principle components, α- and β-santalol. Hence the current study was undertaken to assess the protective effects of EISO, and α- and β-santalol against neurotoxic (6-OHDA/6-hydroxydopamine) and proteotoxic (α-synuclein) stresses in a Caenorhabditis elegans model. Initially, we found that EISO and its principle components exerted an excellent antioxidant and antiapoptotic activity as it was able to extend the lifespan, and inhibit the ROS generation, and germline cell apoptosis in 6-OHDA-intoxicated C. elegans . Further, we showed that supplementation of EISO, and α- and β-santalol reduced the 6-OHDA and α-synuclein-induced Parkinson's disease associated pathologies and improved the physiological functions. The genetic and reporter gene expression analysis revealed that an EISO, or α- and β-santalol-mediated protective effect does not appear to rely on DAF-2/DAF-16, but selectively regulates SKN-1 and its downstream targets involved in antioxidant defense and geroprotective processes. Together, our findings indicated that EISO and its principle components are worth exploring further as a candidate redox-based neuroprotectant for the prevention and management of age-related neurological disorders.